Formation of Poultry Meat Flavor by Heating Process and Lipid Oxidation - Purba, Maijon (Indonesian Bulletin of Animal and Veterinary Sciences, 2014)
Flavor is an important factor in the acceptance of food. Flavor of poultry meat is naturally formed through a specific process of heating, where various chemical reactions complex occurred among nonvolatile precursors in fatty tissue or in lean tissue. The main flavor in the form of volatile and nonvolatile components play a major influence on the acceptance of various processed meat, especially the taste. Removal of sulfur components decreases meat flavor (meaty), while removal of carbonyl compounds decrease the specific flavor and increases common flavor of the meat. Poultry meat has a fairly high fat content that easily generates lipid oxidation. Lipid oxidation in poultry meat is a sign that the meat was damaged and caused off odor. Addition of antioxidants in the diet can inhibit lipid oxidation in the meat. Lipids interaction with proteins and carbohydrates is unavoidable during the thermal processing of food, causing the appearance of volatile components. The main reaction in meat flavor formation mechanism is Maillard reaction followed by Stecker reaction and degradation of lipids and thiamine. They involve in the reaction between carbonyl and amine components to form flavor compounds, which enhance the flavor of poultry meat.Â Key words: Flavor, off flavor, poultry meat, lipid oxidation, antioxidant